Faecal composition after surgery for Hirschsprung's disease. Issue 10 (October 1976) - Postuma, R; Corkery, J J; Beetham, R; Raine, D N
Abstract : Diarrhoea and perianal excoriation occur frequently after the endorectal pull-through operation for Hirschsprung's disease. A new method of faecal analysis was performed on 3-day stool collections in 17 postoperative Hirschsprung patients and in 14 normal children, in order to define the faecal abnormality and to establish the cause of perianal excoriation in these patients. Loose stools in postoperative patients were deficient in dry solid content and contained an excess of extractable faecal water. This also had a raised electrolyte concentration, particularly with respect to sodium. Total daily output of faecal water was normal. Formed stools from postoperative patients were also deficient in drysolids but had a normal extractable water content. Excess extractable faecal water, the main abnormality of loose stools in these patients, is the result of abnormal water absorption from the distal colon. Perianal excoriation in these patients is most closely associated with the concentration of sodium in faecal water.